Lights and Shadows about the Effectiveness of IVF in HIV Infected Women: A Systematic Review. (8th December 2015) - Marques, Catarina; Guerreiro, Cristina; Soares, Sérgio Reis
Abstract : Background . HIV infected women have higher rates of infertility. Objective . The purpose of this literature review is to evaluate the effectiveness of fresh IVF/ICSI cycles in HIV infected women. Materials and Methods . A search of the PubMed database was performed to identify studies assessing fresh nondonor oocyte IVF/ICSI cycle outcomes of serodiscordant couples with an HIV infected female partner. Results and Discussion . Ten studies met the inclusion criteria. Whenever a comparison with a control group was available, with the exception of one case, ovarian stimulation cancelation rate was higher and pregnancy rate (PR) was lower in HIV infected women. However, statistically significant differences in both rates were only seen in one and two studies, respectively. A number of noncontrolled sources of bias for IVF outcome were identified. This fact, added to the small size of samples studied and heterogeneity in study design and methodology, still hampers the performance of a meta-analysis on the issue. Conclusion . Prospective matched case-control studies are necessary for the understanding of the specific effects of HIV infection on ovarian response and ART outcome.